A Pedagogical Perspective on the Reiteration of Blended Learning: A Review Paper vis-a-vis Pre-Post Pandemic - Glen Nolasco; Graciela Ann David Escoto; Frienchie Ann Bais Yamauchi; Michael Bryan Gagaoin Rosilla; Marilyn S. Arcilla (Research Synergy Foundation, 2024)
The COVID-19 pandemic has changed the paradigm of traditional education to alternative learning modalities. One of these changes was the use of blended learning in the educational system. Blended learning is a pedagogical approach that combines face-to-face instruction with online learning as a viable solution to address the challenges introduced by the pandemic. The approach began to gain popularity in the Philippines during the post-pandemic period. The use of ICT to facilitate distance learning was emphasized during the lockdown period. As COVID-19 cases declined and classes started re-opening, adherence to health protocols, such as social distancing, was implemented. In this regard, limitations in the class population and outside exposure were addressed by the blended learning approach. Hence, this review article reiterates the pedagogical perspective of blended learning in the educational system during the global and local health crises. This paper reviews the nature of blended learning in the educational system by examining the various theories and models used, more specifically focusing on the advantages and disadvantages of blended learning in basic education. The reiteration of blended learning during the pandemic and related studies are also some focal points of this review article. In brief, blended learning refines the traditional modalities used in the educational system into something suitable for post-pandemic. It integrates the use of digital materials to create a more effective and engaging mode of delivery for learning. With these insights, the development of blended learning is inevitable in the education sector.